Meningkatkan Self-Efficacy Pasien Hemodialisis melalui Program Afirmasi Positif - Harisa, Akbar; Putri, Ayu Anggita; Rodiah, Isyatir; Syarif, Intan; Marampa, Anugrah Christy; Toding, Dewiyanti; Yodang, Yodang (LPPM Universitas Bumigora, 2024)
Positive affirmations are positive statements that are used to get rid of negative thoughts where these statements are instilled in oneself. The purpose of this activity is to increase the self-efficacy of hemodialysis patients. The method of carrying out structured activities such as screening for patients, education preparation, delivering teaching to the patient, and conducting monitoring and evaluation. This activity results, mostly patients reported that their positive affirm and self-efficacy are getting better. Positive affirmations can be given to someone who is experiencing powerlessness or fatigue about what is currently being lived. Based on our survey we found that the majority of the hemodialysis patients reported the powerless, and that impact self-efficacy of the patients. In order to improve self-efficacy among those patients we delivered an affirmation therapy education for self-efficacy improvement. The impact of this activity is to assist people in reducing stress and feeling depression leading to healthy life and better life.